Adolescents Are More Likely to Help Others on Days They Take Risks and Crave Social Connections. (14th December 2021) - Armstrong‐Carter, Emma; Bibby, Emily S.; Burroughs, Melissa; Flannery, Jessica E.; Nelson, Benjamin W.; Duell, Natasha; Prinstein, Mitch J.; Telzer, Eva H.
Abstract : This study examined how adolescents' risk‐taking behaviors were related to their prosocial behaviors on a daily level and how this association differed depending on adolescents' daily and average levels of sensation seeking and social craving. Adolescents ( N  = 212; M age  = 15 years) completed daily diaries for 14 days. Adolescents were more likely to engage in prosocial behavior on days when they also took risks, but only when they also felt high levels of social craving. The daily link between risk‐taking and prosocial behavior did not vary based on daily or individual differences in sensation seeking. Results suggest that when adolescents feel highly motivated to connect with others, their risk‐taking and prosocial tendencies co‐occur on a daily basis.